Culture of Siri' Na Pacce As Part of Legal Awareness of the Bugis-Makassar Community - Wahyudi Gani, Andika; Abdul Gani, Hamsu (KnE Social Sciences, 2024)
This research provides a description of the main values of the Siri’ na Pacce culture of the Bugis-Makassar community and investigates the factors contained in the Siri’ na Pacce values that shape the legal awareness of the Bugis-Makassar community. The study includes normative and empirical legal research, using a sociological jurisprudence approach. The flow of sociological jurisprudence requires that in the process of forming legal reforms it must pay attention to public awareness and also pay attention to legal values of the society. Based on the research objectives of this law are descriptive legal research, explicative legal research, and prescriptive legal research. The value of Siri’ na Pesse (in Bugis terminology) or Siri’ na Pacce (in Makassar terminology) in Bugis-Makassarese society teaches about decency in the form of recommendations, prohibitions, rights and obligations that dominate human actions to protect and defend their honor. Three research locations inhabited by Bugis and Makassarese people in South Sulawesi Province were selected for the study, namely Bone Regency, Gowa Regency, and Jeneponto Regency. The results of the study show that the existence of Siri’ na Pacce as an abstract value that lives in the midst of Bugis-Makassarese society, this cultural value undergoes a process of concretization in the form of the Pangngaderreng system (legal system) which is then actualized into the five legal norms contained in Pangngaderreng (Ade, Talk, Wari, Rapang, and Sara). Enforcement of these norms is in the framework of realizing the objectives of law, namely justice, legal certainty, and expediency. The realization of the three legal objectives makes the values of Siri’ na Pacce even stronger in the eyes of the community, which is seen as a form of legal awareness. Keywords: Siri’ na Pacce culture, legal awareness, Bugis society